Development of digital comics to improve reading comprehension and self-efficacy of grade V students - Adisty Ameliya Putri; Sri Sukasih (JINoP (Jurnal Inovasi Pembelajaran), 2025)
This study investigates the development of digital comics as an innovative instructional medium aimed at improving both reading comprehension and self-efficacy among fifth-grade elementary school students. The research is grounded in the context of declining student interest and performance in reading, particularly in understanding explanatory texts as mandated in the Indonesian language curriculum. The objective is to provide an engaging, accessible, and pedagogically sound media format that aligns with student learning characteristics and enhances their academic engagement. The research adopts a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were obtained through qualitative and quantitative methods including interviews, classroom observations, student questionnaires, and pretest-posttest instruments. The developed media was validated by material experts, media experts, and classroom practitioners. The digital comics were designed using Canva and distributed interactively through Heyzine, incorporating structured narrative elements and visual appeal to support literacy development. The validation results revealed a high feasibility score of 91.59%, and the effectiveness test yielded an average n-gain score of 0.6793, signifying a moderate yet meaningful improvement in students’ reading comprehension. Furthermore, students’ self-efficacy scores reached 75.82%, placing them in the “good” category. These findings suggest that digital comics are not only effective in enhancing cognitive literacy but also in supporting students’ confidence and motivation in the learning process. This research implies that digital comics can serve as a valuable pedagogical tool in elementary education. Future implementations should explore broader accessibility, including offline versions, and their integration into other subject.